Semiconductor Electrochemistry and Localised Corrosion - Rangel,C.M. (2004)
In the present work, the electronic structure of the passive film formed on austenitic stainless steel of the 304 type and its implications on the initiation of localised corrosion are investigated taking into account concepts developed in semiconductor physics and semiconductor electrochemistry. Capacitance measurements (Mott-Schottky approach), show that the susceptibility of AISI 304 stainless steel to stress corrosion cracking (SCC) in boiling chloride containing aqueous solutions is closely linked to the formation of a chromium rich passive oxide film with p-type semiconductivity. A small polarisation is required to drastically change the electric field at the film-electrolyte interface, as a consequence of the high doping level of the passive film. Initiation of the SCC phenomenon is described as the consequence of localised changes in the semiconductive properties of the passive film.